Aspects of moat formation in tropical cyclone eyewall replacement cycles - Rozoff, Christopher Michael, author; Schubert, Wayne H., advisor; Oprea, Iuliana, committee member; Cotton, William R., committee member; Johnson, Richard H., committee member (Colorado State University. Libraries, 2007)
In order to increase our fundamental understanding of rapid intensity change in tropical cyclones (TCs), the evolving kinematic and thermodynamic conditions in TC eyewall replacement cycles and attendant moats are examined in this study. With the assistance of theory, observations, and cloud-resolving numerical simulations, the response of convection to typical environments outside of intense TC cores is addressed. In our analysis of the environmentally-dependent behaviors of deep, convective clouds, we consider new hypotheses and insights in rainband dynamics and concentric eyewall formation. Re-visiting basic stirring criteria for two-dimensional flows, we derive simple rules-of-thumb for the existence of deep, moist convection in environments of intense horizontal strain. These results are compared with numerical integrations of vorticity in a nondivergent barotropic model. The kinematic and thermodynamic environments during eyewall replacement cycles are documented through observational case studies incorporating dense arrays of dropsondes and aircraft data. Moat observations are compared with idealized balanced vortex theory to increase our understanding of moat dynamics. In addition, idealized cloud-resolving, numerical simulations are carried out to address how horizontal strain, vertical shear and the thermodynamic basic state influence individual deep, convective clouds in TC-like environments. We find that regions of intense horizontal strain are quite common outside of intense TC eyewalls. Observations show this region is also marginally unstable at low-levels and that, as a moat forms in concentric eyewall formation, the region outside of an inner eyewall acquires eye-like thermodynamics. Consistent with observations, idealized solutions to an axisymmetric, balanced-vortex model show that subsidence rapidly increases in the moat region as a secondary eyewall forms. In the midst of marginal convective instability, our idealized cloud simulations suggest a practical threshold for adverse filamentation of convective clouds. However, convection exhibits increasing resiliency to adverse strain under increasingly favorable thermodynamic conditions. Also, rich dynamics, which are most likely at work in concentric eyewall and moat formation and in rainbands, are revealed in our systematic exploration of convective behaviors across a wide spectrum of horizontal and vertical shears.
Keywords: atmosphere; atmospheric sciences